Prevalence of Sleep Disturbance Among DPT Students : Prevalence of Sleep Disturbance Among Students - Nadeem, Iqra; Fatima , Raees; Avaid, Ana; Anwar, Sobia; Nazik, Naila; Rani, Zunaira; Shakoor, Emaan; Asif, Qurat ul Ain; Nizam, Hifsa; Kompal, Rabab (Pakistan Journal of Health Sciences, 2023)
Sleeping is essential for student physical as well as mental health. Sleep disturbance is distressing state that affect quality of work. Objective: To determine the sleep disturbance in DPT students. Methods: This observational study recruited 884 participants out of which 800 filled the questionnaire with mean age 21.54 ±1.76 from different medical universities and medical colleges of Punjab. Non probability convenient sampling technique was used. Both male and female students of all the years of DPT were included. Students with psychiatric illness, chronic medical illness, smoking and taking drugs excluded from the study. The effects of insomnia were checked by Athens Insomnia Scale (AIS) questionnaire. For data analysis SPSS version 26 was used. Results: Mean age of the physical therapy students was 21.54 ±1.76. Out of 800, 61.75% students were insomniac. Most of the students had unsatisfactory sleep quality (55.87%), awakening at the night time (62%), and day time sleepiness (76.25%). Conclusion: According to present study prevalence of sleep disturbance was very high among physical therapy students